Postpartum Granulomatous Hypophysitis: A Case Study, Review of the Literature, and Discussion of Pathogenesis - Upasana Joneja; D. Craig Hooper; James J. Evans; Mark T. Curtis (Case Reports in Pathology)
Hypophysitis is a rare inflammatory condition of the pituitary gland that has three main histologic subtypes: lymphocytic hypophysitis (LH), granulomatous hypophysitis (GH), and xanthomatous hypophysitis (XH). Among these, LH is the most common and is strongly associated with the postpartum state, while XH is the least common. Many hypophysitis cases have been reported in the literature but only a few cases of postpartum GH have been discussed. Here, we describe a case of GH in a 24-year-old female presenting eleven days postpartum. We also review the current literature on postpartum GH and discuss the possible alterations in the immune environment during and after pregnancy that could explain this phenomenon. With more cases of GH being reported, the commonalities of female predominance, postpartum time of presentation, and occasional spontaneous resolution between LH and GH lend support to the theory that these two diseases likely represent spectrums of a single immunologic disorder.